An eschatological imagination: a revisionist Christian eschatology in the light of David Tracy's theological project - Shields, John M. (American university studies / 7, 2008)
The contours of contemporary eschatological reflection -- Structuring the discussion of contemporary Christian eschatology -- Gerhard Sauter -- Jürgen Moltmann -- The Roman Catholic discussion : Zachary Hayes, Dermot Lane, and the debt to Karl Rahner -- Thematic convergences along the contours of eschatological reflection : the work of Stephen Williams and the contemporary discussion -- The eschatological dimensions of the theological project of David Tracy in blessed rage for order -- Plurality -- The notion of limit -- The implicit eschatological dimension -- The explicit eschatological dimension disclosing an eschatological mode of being-in-the-world -- The eschatological dimensions of the theological project of David Tracy in the analogical imagination -- The nature of the classic and its appropriateness for a public systematics -- The religious classic : manifestation of the whole by the power of the whole -- The Christian classic : eschatological wholeness manifested finally and decisively -- The eschatological shape that a life of wholeness can take -- The eschatological dimensions of the theological project of David Tracy in plurality and ambiguity -- Continuities but also radical intensifications -- The eschatological in radical interruptions -- The interruption of truth -- The interruption of language -- The interruption of history and the other as mystery -- The shape of hope finally in and in spite of radical interruptions -- An eschatological imagination : a revisionist Christian eschatology in the light of David Tracy's theological project -- The contemporary situation -- Locating Tracy -- Shaping an eschatological imagination -- Interruption, future and hope -- Truth in action and rhetoric -- Active hopes arsenal of practical strategies